Scientific Literacy as a Differentiated Learning Strategy to Improve Students Science Literacy Competence - Syarif Rizalia; Hilda Ayu Melvi Amalia; Rusdi Awan; Sukmawati Sukmawati; Bidasari Bidasari; Sulaiman Sulaiman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aimed to: (1) assess the level of students’ science literacy competence on the topic of the human movement system; (2) investigate the effect of science literacy strategies on students’ science literacy competence in the same topic; and (3) evaluate the effectiveness of science literacy as a differentiated learning strategy to enhance students’ literacy competence. A pre-experimental design with a control group pretest-posttest was employed, involving two 11th-grade science classes at MAN 1 South Konawe as the experimental and control groups. Research instruments included a science literacy-based written test on the human movement system and an observation sheet to monitor instructional implementation. Data were analyzed using descriptive and inferential statistics, including normality and homogeneity tests, independent t-tests, and N-Gain analysis to evaluate the effectiveness of the literacy-based strategy. Results indicated that students’ average pretest scores were categorized as basic prior to the intervention. Following the implementation of the science literacy strategy, the experimental class demonstrated significant improvement, reaching a competent category, with posttest scores exceeding those of the control group. N-Gain analysis confirmed that the science literacy strategy was more effective in enhancing students’ science literacy competence compared to conventional strategies. These findings suggest that the science literacy approach is a viable alternative for promoting conceptual understanding and critical thinking skills, particularly in biology education focused on the human movement system. Therefore, its implementation in madrasa biology learning is recommended to improve the quality of science literacy-based education.Keywords: science literacy, student competence, human movement system, learning effectiveness